Study of DI’s Way Daily Layout in Hermeneutics Viewed from its Layout Elements - Asthararianty; Fanny Lesmana; Yeremia Tulude Ambat (LPPM Stikosa - AWS, 2022)
DI's Way is present as a new media in the world of print media. Print media originating from Surabaya, and for Surabaya residents. It looks like a magazine but is published every day, has a cover layout that is not like a magazine or newspaper. The cover design, in this case, especially the layout, has an aesthetic to determine the mass media, especially print, whether the media will sell or not. However, this daily is claimed to have many fans, both in its initial form, namely a website, to becoming a daily printed in color. This study uses a qualitative method with a hermeneutic approach to explore the impression of what the cover layout design shows that is not like a magazine or newspaper to Surabaya. The hermeneutic method is carried out by interpreting the data seen in the DI's way cover design, layout theory, and also matters related to Surabaya. This data mining is done by looking at the cover layout design in terms of the use of grids, margins, and also text and image elements. The results that can be seen are as a DI's way daily like a newspaper or newsletter that has a template for each edition with a cover layout showing the impression that the main interest of this media is to be able to tell important news to the City of Surabaya, by always using a large size for the main news photo and also for the text element (headline) but the arrangement can still be followed as a comfortable reading flow. A large portion seems to want to show the impression of the characteristics of the City of Surabaya as a city of heroes which has a great and passionate fighting spirit. Meanwhile, supporting news is placed below it according to the order of its news value, showing the impression of the vision that the City of Surabaya has in building a city that is more advanced from all aspects. In addition, grid management displays the impression of being a local mass media that is regularly reported in its media according to the identity of a daily media that has a news order position like an inverted pyramid.